Populasi Bakteri Tanah pada Piringan Tanaman Kelapa Sawit Akibat Pemberian Pupuk NPK Komplit - Netanya Panggabean; T. Sabrina; Kemala Sari Lubis (Universitas Sumatera Utara, 2016)
Soil biota plays an important role several processes in soil. They are enchancing plant growth as inorganic fertilizer such as NPK complete fertilizer. This research was conducted to study population of some species of bacteria at Gajah Village, Sei Balai Subdistrict, Batubara District. The research was a survey by purposive sampling method that aimed to compare soil bacterial population (Azotobacter spp., Bacillus spp. and Lactobacillus spp.) in the oil palm’s weeded circle. The research was done by taking 60 soil samples in the oil palm’s weeded circle. The result showed that the population of bacteria Azotobacter spp. around the weeded circle of oil palm applied with the NPK complete differed with the oil palm’s weeded circle that has not been given a NPK complete fertilizer. The relationship between the occurrences of soil bacteria with the soil properties showed that the presence of Bacillus spp. affected the water soil content and the nitrogen total. Keywords: Azotobacter spp., Bacillus spp., Lactobacillus spp., NPK complete fertilizer